PERAN COUNTRY OF ORIGIN PADA PERILAKU KONSUMEN NEGARA BERKEMBANG - Salma Fauziyyah; Dini Optimasi; Puji Lestari Reski Fitriani (UPT Penerbitan Universitas Jember)
The purpose of this analysis is to examine which then can be used as information about the role of country of origin on consumer behavior developing countries. Based on this study the authors hope to provide a reference solution that can be used to overcome the problem of the people of Indonesia, especially in economic terms, both for governments, businesses, banks, academia and the general public. The methods used to analyze and solve problems in this paper is to examine the books of previous studies which could serve as a reference. The conclusion of the article the results of this thinking is that the country of origin can form consumers perceived quality and cause as well as inhibit consumer purchase intention. Country of origin of a product plays a role in shaping the quality perceived by the consumer and would later influence consumer purchase intent. Thus, companies must be able to face the competitive strategies of various countries. The formation of the ASEAN Economic Community (AEC) has facilitated consumers to see and enjoy the products from various countries. Therefore, when companies promote their products to the global market, they also have to consider the image of the country of origin.